Dynamics of Balancing Social Welfare and Economic Benefit in Akzonobel’s CSR Governance in Indonesia - Rino Ardhian Nugroho; Septyanto Galan Prakoso; Meisya Putri Intan Cahyani; Listya Wahyuningtyas Putri; Ferdian Ahya Al Putra (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2022)
Corporate Social Responsibility has grown as an issue in corporate governance in recent years.  By having such programs, a private company might seem as having a social responsibility towards its social surroundings. In October 2020, no less than 19.056 studies had been conducted on this subject in various contexts. Even though plenty of research was conducted in the area, there is still limited understanding of how CSR helps a Multinational Company (MNC) during a crisis. This study will analyze the role of private companies (as the example is AkzoNobel) in providing for public needs while gaining economic benefit simultaneously. This study will use a qualitative descriptive method, with document analysis as a data collection technique. For analyzing the data this study will use Miles, Huberman, and Saldana’s approach to data reduction and display. The result indicates that a comprehensive CSR program combined with strong corporate culture helps an MNC in surviving its operation despite being in the middle of domestic challenges. This research may serve as a checkpoint for further study on CSR in society as one of the social-cultural issues.